TGF-β-activated Kinase 1 (Tak1) Mediates Agonist-induced Smad Activation and Linker Region Phosphorylation in Embryonic Craniofacial Neural Crest-derived Cells - Kenji Yumoto; Penny S. Thomas; Jamie Lane; Kouichi Matsuzaki; Maiko Inagaki; Jun Ninomiya‐Tsuji; Gregory J. Scott; Manas K. Ray; Mamoru Ishii; Robert E. Maxson; Yuji Mishina; Vesa Kaartinen (2013)
Although the importance of TGF-β superfamily signaling in craniofacial growth and patterning is well established, the precise details of its signaling mechanisms are still poorly understood. This is in part because of the concentration of studies on the role of the Smad-dependent (so-called “canonical”) signaling pathways relative to the Smad-independent ones in many biological processes. Here, we have addressed the role of TGF-β-activated kinase 1 (Tak1, Map3k7), one of the key mediators of Smad-independent (noncanonical) TGF-β superfamily signaling in craniofacial development, by deleting Tak1 specifically in the neural crest lineage. Tak1-deficient mutants display a round skull, hypoplastic maxilla and mandible, and cleft palate resulting from a failure of palatal shelves to appropriately elevate and fuse. Our studies show that in neural crest-derived craniofacial ecto-mesenchymal cells, Tak1 is not only required for TGF-β- and bone morphogenetic protein-induced p38 Mapk activation but also plays a role in agonist-induced C-terminal and linker region phosphorylation of the receptor-mediated R-Smads. Specifically, we demonstrate that the agonist-induced linker region phosphorylation of Smad2 at Thr-220, which has been shown to be critical for full transcriptional activity of Smad2, is dependent on Tak1 activity and that in palatal mesenchymal cells TGFβRI and Tak1 kinases mediate both overlapping and distinct TGF-β2-induced transcriptional responses. To summarize, our results suggest that in neural crest-derived ecto-mesenchymal cells, Tak1 provides a critical point of intersection in a complex dialogue between the canonical and noncanonical arms of TGF-β superfamily signaling required for normal craniofacial development. Although the importance of TGF-β superfamily signaling in craniofacial growth and patterning is well established, the precise details of its signaling mechanisms are still poorly understood. This is in part because of the concentration of studies on the role of the Smad-dependent (so-called “canonical”) signaling pathways relative to the Smad-independent ones in many biological processes. Here, we have addressed the role of TGF-β-activated kinase 1 (Tak1, Map3k7), one of the key mediators of Smad-independent (noncanonical) TGF-β superfamily signaling in craniofacial development, by deleting Tak1 specifically in the neural crest lineage. Tak1-deficient mutants display a round skull, hypoplastic maxilla and mandible, and cleft palate resulting from a failure of palatal shelves to appropriately elevate and fuse. Our studies show that in neural crest-derived craniofacial ecto-mesenchymal cells, Tak1 is not only required for TGF-β- and bone morphogenetic protein-induced p38 Mapk activation but also plays a role in agonist-induced C-terminal and linker region phosphorylation of the receptor-mediated R-Smads. Specifically, we demonstrate that the agonist-induced linker region phosphorylation of Smad2 at Thr-220, which has been shown to be critical for full transcriptional activity of Smad2, is dependent on Tak1 activity and that in palatal mesenchymal cells TGFβRI and Tak1 kinases mediate both overlapping and distinct TGF-β2-induced transcriptional responses. To summarize, our results suggest that in neural crest-derived ecto-mesenchymal cells, Tak1 provides a critical point of intersection in a complex dialogue between the canonical and noncanonical arms of TGF-β superfamily signaling required for normal craniofacial development.